2016
DOI: 10.18632/oncotarget.9503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of epidermal growth factor receptor inhibitors in combination with chemotherapy in advanced non-small cell lung cancer: A meta-analysis of randomized controlled trials

Abstract: The role of a combination of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and chemotherapy for non-small-cell lung cancer (NSCLC) has not been well established. To clarify this problem, we performed a meta-analysis with 15 studies identified from PubMed, EMBASE and the Cochrane Library. We found that the combined regimen had a significant benefit on progression-free survival (PFS) (hazard ratio (HR) = 0.80; 95% CI = 0.71–0.90; P < 0.001) and the objective response rate (ORR) (RR = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…De-escalated dosages of afatinib showed a greater tendency towards longer periods of TTF in this study (Figure 2 ). These results are consistent with the results of other trials of afatinib therapy [ 6 , 13 , 14 , 15 ]. The suspension of high-dosage afatinib therapy usually stems from the occurrence of higher grade diarrhea and cutaneous toxicity as adverse events.…”
Section: Discussionsupporting
confidence: 92%
“…De-escalated dosages of afatinib showed a greater tendency towards longer periods of TTF in this study (Figure 2 ). These results are consistent with the results of other trials of afatinib therapy [ 6 , 13 , 14 , 15 ]. The suspension of high-dosage afatinib therapy usually stems from the occurrence of higher grade diarrhea and cutaneous toxicity as adverse events.…”
Section: Discussionsupporting
confidence: 92%
“…benefit was shown in EGFR mutation-positive patients by subgroup analysis (10). Cheng et al also demonstrated that the addition of pemetrexed to gefitinib in first-line treatment improved PFS compared with gefitinib alone in Ease Asian patients with advanced EGFR-mutant lung cancer (HR, 0.68; 95% CI, 0.48 to 0.96; one-sided P=0.014; two-sided P=0.029) (11).…”
Section: Editorialmentioning
confidence: 98%
“…In patients whose tumours harbours an activating EGFR mutation, EGFR TKIs should be used as first-line therapy [ 6 9 ], whereas for the rest of NSCLC cases, standard treatment currently consists of platinum-based doublet chemotherapy. Gefitinib, erlotinib and afatinib show higher response rates and longer progression free survival than chemotherapy in those patients, as tested in several clinical trials exhibiting consistent results [ 10 20 ], all of them favouring the target therapy.…”
Section: Introductionmentioning
confidence: 98%